Chemical constituents from the leaves of Terminalia catappa L. (Combretaceae) - Hung, Ho Dac; Doan Duy Tien; Nguyen Thi Ngoan; Duong, Ba Thi; Do Quoc Viet; Pham Gia Dien; Bui Kim Anh (Vietnam Journal of Science and Technology, 2022)
Terminalia catappa L. (cây Bàng) belongs to the family Bàng (Combretaceae), is a large tree species living mainly in the tropics. The phytochemical studies of this plant have only focused on the volatile fraction and tannins. The main components in the plant include terpenes, flavonoids, tannins, saponins and phytosterols. T. catappa species has been recognized as an important medicinal plant. In traditional medicine, T. catappa leaf, bark and fruit are used in treating dysentery, rheumatism, cough and asthma. The fruit is also helpful in the treatment of leprosy and headaches and the leaves are specifically used in getting rid of intestinal parasites, treatment of eye problems, wounds, and liver problems. Due to its rich medicinal ingredients, the leaves and bark are used in various herbal medicines for different purposes. This study aims to characterize the phyto-chemical constituents present in the leaf extracts of Terminalia catappa using chromatographic and spectroscopicmethods. Four flavonoids, tectochrysin (1), luteolin (2), kaempferol 3,7,4′-trimethyl ether (4), and kaempferol (5), one phenolic, gallic acid (3), were isolated from the ethylacetate fraction of the leaves of Terminalia catappa L.. Their structures were elucidated on the basis of spectroscopic analysis and comparisons with known related compounds. Compounds 1 and 4 were reported for the first time from the leaves of Terminalia catappa.